2020
DOI: 10.1155/2020/8825547
|View full text |Cite
|
Sign up to set email alerts
|

Mental Fatigue Has Great Impact on the Fractal Dimension of Brain Functional Network

Abstract: Mental fatigue has serious negative impacts on the brain cognitive functions and has been widely explored by the means of brain functional networks with the neuroimaging technique of electroencephalogram (EEG). Recently, several researchers reported that brain functional network constructed from EEG signals has fractal feature, raising an important question: what are the effects of mental fatigue on the fractal dimension of brain functional network? In the present study, the EEG data of alpha1 rhythm (8-10 Hz)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…By aiming to evaluate the brain fatigue state, Li et al analyzed the influence of mental fatigue on the fractal dimension of the brain function network. ey found that the increase in mental fatigue was positively correlated with the fractal dimension, while the fractal dimension of the weighted network was more sensitive to mental fatigue [28]. ese results can support the research results in the present work.…”
Section: Mental Fatigue Evaluation Based On Binary Networksupporting
confidence: 90%
“…By aiming to evaluate the brain fatigue state, Li et al analyzed the influence of mental fatigue on the fractal dimension of the brain function network. ey found that the increase in mental fatigue was positively correlated with the fractal dimension, while the fractal dimension of the weighted network was more sensitive to mental fatigue [28]. ese results can support the research results in the present work.…”
Section: Mental Fatigue Evaluation Based On Binary Networksupporting
confidence: 90%
“…Network features can reflect the functional integration and local aggregation of information between brain regions when performing mental tasks [ 32 , 45 , 47 ]. In this study, we analyzed brain network reorganization during task switching before and after mental fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al used EEG data on human mental fatigue to construct a brain function network, and proposed a modified greedy coloring algorithm to calculate the fractal dimension of binary and weighted brain function networks. The results showed that the fractal dimension increased with the increase of mental fatigue [20]. Mental fatigue characteristics in some brain leads are not obvious, and the noise interference of redundant channels increases the computational complexity.…”
Section: Introductionmentioning
confidence: 97%